Energy Transfer by Resonance Coupling - Heinz Zenkner; Werachet Khan-Ngern (Institute of Advanced Engineering and Science, 2013)
This paper presents the research work focusing on the possibility to transmit power with a high power densitiy and a high efficiency. The applications of power supply require a smaller size, lower weight with a good energy on-board management. This work shows not only the possibility of wireless power transfer, but also the biological effect is taken into account for the safety precaution of human use. The system is described and set up using the resonance coupling effect and impedance adaption for multi-stage conversion. The transmitting power up to 180W is applied at a frequency of 6.78 MHz across a gap in the range between 30 mm to 80 mm. The experimental results show that the maximum efficiency up to 88 % has been achieved. The maximum transmitted power density reaches up to 0.14 W/mm2. High power can be transmitted using resonant coupling with high efficiency. Coupling coil characteristics significantly affect wireless power system losses. High power density of the active areas can be in the high range of 0.14 W/mm2. Resonance coupling can be applied in short range applications keeping EMC and EMF restrictions.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3938